Effect of temperature on the daily increment deposition in the Otoliths of European sardine Sardina pilchardus (Walbaum, 1792) Larvae - Soares, Claudia (2021)
Otolith microstructure analysis is a valuable tool to evaluate the relationship between larval age and growth and how it relates to environmental variability. Otolith growth and daily increment deposition were analyzed in sardine (Sardina pilchardus) larvae reared in the laboratory under different temperatures (13, 15, and 17 ◦C), with a diet rich in microalgae, rotifers, and copepods Acartia grani. The number and width of growth increments, first-check and otolith diameter were determined in the otoliths and then related to larval age and total length. At hatching, the sagittal otoliths consisted of a lenticular core with a diameter of 10.56 µm (±1.07 µm SD). Somatic growth increased with the increasing temperature and the growth rate of larvae reared at 13 and 15 ◦C was significantly lower than for larvae reared at 17 ◦C. At 17 ◦C, otoliths exhibited a higher diameter with wider increments than at 13 ◦C. There was a high variability of increment counts-at-age for larvae reared within the same temperature treatment. The increase of growth increments with larval size was higher for larvae reared at 17 ◦C until 35 days post-hatching than those growing at 15 ◦C. Scanning electronic microscopy confirmed that increments are deposited daily, with an average width smaller than 1 µm and as low as 0.33 µm, therefore impossible to distinguish using light microscopy. At colder temperatures, larval otoliths had thinner and less marked increments and lower growth rates, which can lead to incorrect age determinations. The effect of temperature on the otolith microstructure can help in identifying strong temperature gradients experienced by wild sardine larvae.